(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: This study aims to (1) assess nurses’ perceptions of the family-centered care (FCC) model in pediatric practice, and (2) describe the feasibility and extent of applying FCC principles in actual caregiving at the Pediatric Center of Hue Central Hospital. Methods: A cross-sectional descriptive study was conducted from August 2021 to June 2022, involving 67 nurses at the Pediatric Center of Hue Central Hospital. The study employed the FCC Questionnaire developed by Jina Oh. Results: The main barriers identified include a high nurse-to-patient ratio, limited knowledge of family-centered care (FCC), and low health literacy among family members. Nevertheless, the majority of nurses demonstrated a positive perception of FCC (97%) and a willingness to change (58.2%). The model is perceived as beneficial in improving the quality of care and increasing parental satisfaction. Conclusion: FCC is a suitable model in pediatric nursing practice. Strengthening training programs and systemic support is essential to effectively implement the model in clinical settings.